Strengthening Nation and Character Building in the Study of Islamic Philosophy of Education - Haryono, Merda Budi; Fauzi, Sudar; Sumarna, Andri; Emuh, Dadang; Rosmaula, Ajeng (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2022)
Strengthening Nation and Character Building based on Islamic values has become an urgent need amid global moral crisis, radicalism, and the disorientation of values among the younger generation. This study aims to formulate a concept of Islamic education based on tazkiyah that can shape a complete Muslim personality while contributing to the formation of national character. This study employs a qualitative approach using literature review and content analysis of works by Islamic education scholars, particularly Al-Ghazali and Ahmad Sanusi, selected purposively due to the relevance of their thoughts to the research topic. Data sources include classical and contemporary literature, as well as previous studies discussing Islamic education philosophy, tazkiyah, and character development. The analysis was conducted thematically to identify the concepts, stages, and implementation of tazkiyah in education. The results of the study indicate that tazkiyah encompasses the purification of the soul (tazkiyah al-nafs), the purification of the mind (tazkiyah al-‘aql), and the purification of the body (tazkiyah al-jism), which proceed through three stages—Islam, Iman, and Ihsan—and integrate cognitive, affective, and psychomotor dimensions. This approach is considered relevant to be integrated into the Islamic education curriculum as a strategy for strengthening national character in a holistic manner. The implications of this research are theoretical, enriching the study of Islamic educational philosophy, and practical, serving as a reference for educators and policymakers in designing tazkiyah-based learning strategies.